2020
DOI: 10.3389/fmed.2020.571597
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab: The Key to Stop Coronavirus Disease 2019 (COVID-19)-Induced Cytokine Release Syndrome (CRS)?

Abstract: The COVID-19 disease is an unprecedented international public health emergency and considerably impacts the global economy and health service system. While awaiting the development of an effective vaccine, searching for the therapy for severe or critical COVID-19 patients is essential for reducing the mortality and alleviating the tension of the health service system. Cytokine release syndrome (CRS) induced by elevated interleukin-6 was recognized to underscore the pathology of severe COVID-19 patients. Inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
1
12
0
2
Order By: Relevance
“…45 The antiinflammatory effect of Apixaban was also observed in the acute phase of ischemic stroke patients. 46 A similar study has revealed that Rivaroxaban caused a significant reduction in the levels of D-dimer and IL-6 in patients with atrial fibrillation. 47 These results indicate that blocking the activity of FXa may be beneficial to prevent the SARS-CoV-2associated coagulopathies and dampen the virus-triggered excessive immune response.…”
Section: Direct Factor X Inhibitormentioning
confidence: 84%
See 1 more Smart Citation
“…45 The antiinflammatory effect of Apixaban was also observed in the acute phase of ischemic stroke patients. 46 A similar study has revealed that Rivaroxaban caused a significant reduction in the levels of D-dimer and IL-6 in patients with atrial fibrillation. 47 These results indicate that blocking the activity of FXa may be beneficial to prevent the SARS-CoV-2associated coagulopathies and dampen the virus-triggered excessive immune response.…”
Section: Direct Factor X Inhibitormentioning
confidence: 84%
“…Tocilizumab, 46 an interleukin-6 inhibitor, and Anakinra-IL1 inhibitor, 47 have been used in the setting of cytokine release syndrome in COVID-19, and recent pilot prospective data suggest a survival benefit if used early in the course of the disease. 48…”
Section: Inflammatory Cytokines Inhibitionmentioning
confidence: 99%
“…The IL-6 receptor antagonist tocilizumab has been used in some cases of severe COVID-19 [ 86 , 87 , 88 , 89 , 90 ]. However, the benefits of tocilizumab for the treatment of COVID-19 are uncertain, [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ] and the Italian Medicines Agency (AIFA) announced on June 18, 2020 that tocilizumab (Actemra) did not improve COVID-19 outcomes [ 91 , 92 , 93 ]. However, a recent meta-analysis reported a reduced mortality prevalence in patients treated with tocilizumab [ 97 ].…”
Section: Diabesity Meta-inflammation and Il-6: The Role In Severmentioning
confidence: 99%
“…Its utility in COVID19 CRS stems both by demonstration of elevated IL6 in severe cases and from its approval for mitigating the CRS induced by chimeric antigen receptor-T cell therapy. 15 TCZ has been used in severe COVID19, including in a fraction of patients with chronic kidney disease. 8 Similar to our case (Figures 1 and 2), they have also shown that TCZ produces rapid improvement in inflammatory markers and radiological parameters.…”
Section: A S Ementioning
confidence: 99%